Computer Anxiety and Computer Attitude in Increasing Staffs’ Interest in Using the System through Perceived Usefulness and Perceived Ease of Use - Hantono Yang; Thomas Sumarsan Goh; Partogian Sormin (PT Mattawang Mediatama Solution, 2022)
Nowadays information technology has developed rapidly therefore the need for Information Technology (IT) has become an essential for every organization, especially in carrying out activities so that an accounting information system implemented properly, can produce reliable financial information for the company. The use of technology in information systems in running a business should consider the usability and convenience of its users so that the system becomes effective. The purpose of this study was to analyze the effects of Computer Anxiety and Computer Attitude in terms of aspects in increasing employees’ interest in operating the system through perceived usefulness and perceived ease of use. The research was conducted on employees in the company in Medan city. The number of research samples were 200 respondents selected by non-probability sampling method. Data was collected by using a questionnaire via google form and literature studies supporting this research. The method used in this study were the Structural Equation Model (SEM) using Partial Least Square (PLS) version 3.0. PLS consists of external relationships (outer model) and internal relationships (inner model), cross loading > 0.7, Composite Reliability, Convergent Validity, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Based on the results of the analysis, it was found that computer anxiety had no effect on interest, while Computer Attitude, Perceived Usefulness, Perceived Ease of Use had an effect on interest